Sustainable Fire-Resistant Biocomposites in the Military Industry: Performance, Challenges, and Opportunities - Rizky Dwiandra Putra; Dangan Waluyo; Timbul Siahaan; Nurul Ilmi; Nurrudin Ahmad; Alvin Muhammad Savero (Indonesian Journal of Advanced Research, 2026)
The growing demand for lightweight, fire-resistant, and sustainable materials in military applications has driven interest in biocomposites as alternatives to conventional materials. This review examines the fire performance of sustainable biocomposites, focusing on degradation behavior, char formation, heat transfer mechanisms, and enhancement strategies using flame retardants and nanomaterials. Nanotechnology-based additives such as nanoclay, graphene, and carbon nanotubes significantly improve thermal stability and reduce heat release rates. The review also highlights multifunctional biocomposites that combine fire resistance with ballistic protection and electromagnetic interference (EMI) shielding. Key challenges include moisture sensitivity, long-term durability, compliance with military fire standards, and manufacturing scalability. Future developments are expected to focus on hybrid multifunctional biocomposites that simultaneously deliver fire resistance, protection, and sustainability for next-generation military systems.